Abstract Algebra - 1
Abstract Algebra - 1
Abstract Algebra - 1
December 2, 2019
1 Group Theory
Definition 1.1. A binary operator ∗ is an operator defined on a set G such that ∀ a, b ∈ G, a ∗
b ∈ G. Alternatively, a binary operator can be regarded as a function ∗ : G × G −→ G where
∀ a, b ∈ G, a ∗ b ∈ G. An algebraic structure is a non-empty set G with one or two binary
operators.
Definition 1.2. An algebraic structure (G, ∗) is a group if it satisfies the following axioms:
• Closure: a, b ∈ G ⇒ a ∗ b ∈ G i.e * is a binary operator.
• Associativity: If a, b, c ∈ G, (a ∗ b) ∗ c = a ∗ (b ∗ c).
• Identity: ∃ a unique element e ∈ G, such that a ∗ e = a = e ∗ a ∀ a ∈ G.This element is the
identity element.
• Inverse: For every a ∈ G, ∃ a unique element b such that a ∗ b = e = e ∗ a.
Definition 1.3. An abelian group is a group (G, ∗) which satisfies the commutativity axiom, viz.
∀ a, b ∈ G, a ∗ b = b ∗ a.
Definition 1.4. Here are a few more defns.
• A set is a groupoid if only the closure axiom is satisfied.
1
4. (Q+ , ×) −→ Set of positive rationals is an abelian group. But Q− can never be a group since
/ Q− .
the identity elements 0,1 ∈
5. (nZ, +) = {0, ±1, ±2, . . .} −→ Abelian group.
6. Set of odd integers is not a group under + or ×, ∵ the sum of two odd integers is always even.
7. The set of irrationals, R − Q can never be a group since 0,1 are rationals.
8. ({an |n ∈ Z}, ×), a ∈ R −→ Abelian group.
9. ({z|z ∈ C, |z| = 1}, ×) −→ Abelian group. Let z1 = r1 eiθ1 , z2 = r2 eiθ2 , r1 = r2 = 1.
Then, z1 .z2 = eiθ1 .eiθ2 = ei(θ1 +θ2 ) = ei(θ2 +θ1 ) = eiθ2 .eiθ1 = z2 .z1
Properties:
• (Zn , +n ) is an abelian group with e = n and a−1 = n − a.
2
0 1 2 3 4
0 0 1 2 3 4
1 1 2 3 4 0
2 2 3 4 0 1
3 3 4 0 1 2
4 4 0 1 2 3
Since every element in the table is also an element of Z5 , the group is closed. From the table, the
identity element can be identified as 0. Moreover, the inverse of each element can also be identified.
The table is also symmetric, implying that the group is abelian.
Example 1.3. Consider the Cayley table of (Z5 , ×5 ).
0 1 2 3 4
0 0 0 0 0 0
1 0 1 2 3 4
2 0 2 4 1 3
3 0 3 1 4 2
4 0 4 3 2 1
The operation is closed. The identity element is 1. But 0 does not have an inverse. So (Z5 , ×5 )
is not a group. If we consider (Z∗5 , ×5 ), e = 1, every element has an inverse and the matrix is
symmetric. Therefore, the group is abelian.
Proof. Let e1 , e2 be two identity elements. Then, e1 .e2 = e1 = e2 .e1 and e2 .e1 = e2 = e1 .e2 .
Equating, we see that e1 = e2 .
Proof. Let x ∈ G and y1 , y2 be two inverses of x. Then, y1 = e.y1 = (y2 .x).y1 = y2 .(x.y1 ) =
y2 .e = y2 .
3. (a−1 )−1 = a ∀ a ∈ G.
Proof. a = a.e = a.(a−1 .(a−1 )−1 ) = (a.a−1 ).(a−1 )−1 ) = (a−1 )−1 )
3
Proof. (a.b)(a.b)−1 = e ⇒ a−1 (ab)(ab)−1 = a−1 .e ⇒ b(ab)−1 = a−1 ⇒ b−1 b(ab)−1 =
b−1 a−1 ⇒ (ab)−1 = b−1 a−1
6. If a2 = e ∀ a ∈ G, G is abelian.
Proof. (ab)2 = e ⇒ abab = e ⇒ ab = b−1 a−1 ⇒ ab = ba. The last equality comes from
a2 = e ⇒ a = a−1 .
7. O(a) = O(a−1 )
8. O(a.b) 6= O(a).O(b)
Proof. Consider the cube roots of unity under multiplication. O(ω) = 3, O(ω 2 ) = 3. But
O(ω.ω 2 ) = O(ω 3 ) = O(e) = 1 6= O(ω).O(ω 2 ).
4
1.3.1 Dihedral Groups
Definition 1.7. An orbit of σ ∈ Sn is a subset g of S such that σ(x) ∈ g ∀ x ∈ g. A cycle is a
permutation σ such that σ has atmost one orbit with more than 1 element. A cycle of length 2 is
called a transposition. A permutation is even (resp. odd) if it can be expressed as the product
of an even (resp. odd) number of transpositions.
1 2 3 4 5 6 7 8
Example 1.6. Consider S8 . Let σ = . The set {1, 2, 5, 6, 7, 8} is an
7 8 4 3 1 5 2 6
orbit of σ. {3, 4} is another orbit. Since there are two orbits with more than 1 element, σ is not a
cycle.
1 2 3 4 5 6 7 8
Let τ = . τ has the orbits {1, 2, 5, 6, 7, 8}, {3}, {4}, of which only one
7 8 3 4 1 5 2 6
has morethan one element. So τ is a cycle.
1 2 3 4 5 6 7 8
Let ρ = . It has the orbits {1}, {2}, {3}, {5}, {6}, {8}, {4, 7}. Clearly,
1 2 3 7 5 6 4 8
ρ is a cycle. In particular, it is a transposition.
Properties
1. Since orbits of a permutation are disjoint, A permutation can be expressed as a product of
its orbits. In example 1.6, σ can expressed as (1 7 2 8 6 5)(3 4), τ as (1 7 2 8 6 5)(3)(4) or
simply (1 7 2 8 6 5) and ρ as (4 7).
2. The product of two cycles need not be a cycle. For example, in S5 , consider σ = (1 5 3) and
τ = (2 1 5). σ ◦ τ = (1 3)(2 5).
3. Every permutation can be expressed as the product of disjoint cycles.
4. Every cycle can be expressed as the product of transpositions. This product is not unique
and does not necessarily contain disjoint transpositions. For example, in S8 (1 3 5 7) =
(1 3)(1 5)(1 7) = (5 1)(5 3)(5 7)
5. Every permutation can be expressed as the product of transpositions.
6. Every transposition has order 2. (a b)(a b) = (a)(b).
7. If σ = s1 .s2 . . . sk , σ −1 = s−1 −1 −1 −1
k sk−1 . . . s2 s1 .
The transpositions are clearly odd. Since ρ1 = (1 2)(1 3) and ρ2 = (1 3)(1 2), these two are even.
The identity permutation is also even, since it can be expressed as the product of 0 transpositions.
5
Proof. Given Sn , let An and Bn be the set of all even and odd permutations respectively. Define
φ : An −→ Bn by φ(σ) = σ ◦ τ , where τ is a fixed transposition in Sn . φ is well-defined, because
if σ1 = σ2 ∈ An , σ1 ◦ τ = σ2 ◦ τ ∈ Bn (adding one transposition to two even permutations make
them odd).
φ is injective. Suppose φ(σ1 ) = φ(σ2 ). Then, σ1 ◦ τ = σ2 ◦ τ . But Sn is a group. Applying right
cancellation, σ1 = σ2 .
φ is surjective. Let µ ∈ Bn . Now, τ −1 ∈ Sn . Then, µ ◦ τ −1 ∈ An and φ(µ ◦ τ −1 ) = µ. Thus
∀ µ ∈ Bn , and element ν = µ ◦ τ −1 ∈ An such that φ(ν) = µ.
Thus φ is a bijective function between sets. So, O(An ) = O(Bn ).
n!
In particular, since O(Sn ) = O(An ) + O(Bn ) = n! and O(An ) = O(Bn ), O(An ) = O(Bn ) = .
2
1.4 Subgroups
Definition 1.8. Let (G, ∗) be a group. Then, a non-empty subset H of G is a subgroup if (H, ∗)
is itself a group. It is denoted by H ≤ G. A subgroup H is improper if H = G or H = e.
Example 1.8. Subgroups of some important groups.
1. (Z, +) - Z, {0}, {nZ|n ∈ Z}
2. (Q, +) - Q, Z, {0}, {nZ|n ∈ Z}
3. (Q, ×) - Q, {1}, {1, −1}, Q+ = {q ∈ Q|q > 0}, {an |a ∈ Q∗ , n ∈ Z}
4. (R∗ , ×) - all the subgroups of (Q∗ , ×), {an |a ∈ R∗ , n ∈ Z}
5. (C∗ , ×) - all of the above, {z|z ∈ C, |z| = 1}, {nth roots of unity|n ∈ Z+ }
6
Theorem 1.3. The intersection of two subgroups H and K of a group G is also a group.
Proof. Suppose a, b ∈ H ∩ K. Then, a, b ∈ H and a, b ∈ K. Since H, K are subgroups, ab−1 ∈ H
and ab−1 ∈ K. Thus a, b−1 ∈ H ∩ K.
7
Proof. Necessary direction: Suppose H ≤ G. Suppose x ∈ HH −1 . x = hk −1 , h, k ∈ H. But since
H is a subgroup, k −1 ∈ H. By closure, hk −1 = x ∈ H. So HH −1 ⊂ H. By definition, e ∈ H −1 .
So, if h ∈ H, h = he = HH −1 . Thus H ⊂ HH −1 .
Sufficient direction: Assume that HH −1 = H. Since H is non-empty, it suffices to prove that
x, y ∈ H ⇒ xy −1 ∈ H. Now, x, y ∈ H ⇒ xy −1 ∈ HH −1 ⇒ xy −1 ∈ H.
Theorem 1.10. Let H, K ≤ G. Then, HK ≤ G ⇐⇒ HK = KH.
Proof. Necessary direction: Assume that HK ≤ G. Since H and K are subgroups, H = H −1 and
K = K −1 . HK = (HK)−1 = K −1 H −1 = KH.
Sufficient direction: Suppose HK = KH. To prove that HK ≤ G, it suffices to prove that
(HK)(HK)−1 = HK.(HK)(HK)−1 = HKK −1 H −1 = H(KK −1 )H −1 = HKH −1 = (HK)H −1 =
K(HH −1 ) = KH.
8
Proof. Let G be a cyclic group and H be a subgroup. Define the set S = {m ∈ Z|am ∈ H}.
Claim.(S, +) ≤ (Z, +)
Because e ∈ H and e = a0 , 0 ∈ S ⇒ S 6= ∅. Suppose m, n ∈ S. Then, am , an , a−n ∈ H, since H is
a subgroup. ⇒ am .a−n = am−n ∈ H by closure. ⇒ m − n ∈ S.
The claim implies that S = {0} or S = {pZ|p ∈ Z} for some p. If S = {0}, H = {e}. If S = {pZ},
H = {am |m ∈ pZ} ⇒ H = {akp |k ∈ Z} =< ap >.
Theorem 1.14. The order of the generator of a cyclic group is equal to the order of the group.
Theorem 1.15. Let G be a cyclic group generated by a, of order d. Then, ak , k < d is also a
generator of G iff k and d are relatively prime.
Corollary. A cyclic group of order d has φ(d) generators, where φ is the Euler totient function.
1 1 1
[φ(n) = n(1 − )(1 − ) . . . (1 − ), where n = pa1 1 pa2 2 . . . pas s is the canonical factorization of n.]
p1 p2 ps
Proof. Let G =< a > of order d. An element ak is a generator iff (k, d) = 1. Thus the number
of generators of G is the number of positive integers less that d relatively prime to d, which is, by
definition φ(d).
Example 1.10 (CSE. 2015). Taking 2 groups of order 4, {e, a, b, c}, construct composition tables
to show that one is cyclic while the other is not.
Construct composition tables for {1, −1, i, −i} and the Klein group, K4 .
Example 1.11 (CSE. 2015). How many generators are there of the cyclic group of order 8?
From Theorem 1.14, we see that if G =< a > is a group of order 8, O(a) = 8. From Theorem 1.15,
we see that an element ak ∈ G is a generator iff (k, 8) = 1. But the number of positive integers less
than 8 relatively prime to 8 is 3. Hence, the group has 4 generators in total.
Example 1.12 (CSE. 2016). Let p be a prime number and Zp be the additive group of integers
modulo p. Show that every non-zero element of Zp generates Zp .
Proof. Zp is a cyclic group generated by the element 1, which has order O(1) = O(Zp ) = p. For
convenience, let an mean a ⊕4 a ⊕4 . . . n times. Then, other generators of the group are the elements
ak , where (k, p) = 1. But since p is prime, every integer 1 < k < p is relatively prime to p. Thus
{ak |1 ≤ k < p} are all generators of Zp . So, every non-zero element of the group is a generator of
the group.
1.6 Cosets
Definition 1.11. Let G be a group and H be a subgroup of G. Then, the set Ha = {ha|h ∈ H} is
the right coset of H in G with respect to a. Similarly, {aH = {ah|h ∈ H}}.
Theorem 1.16. There is a bijective correspondence between the set of all left cosets and the set of
all right coset of a subgroup H in a group G.
9
Proof. Let R = {Ha|a ∈ G} and L = {aH|a ∈ G}. Define f : R −→ L by f (Ha) = a−1 H ∀a ∈ G.
Well-defined and injective:Ha = Hbab−1 ∈ Hab−1 = h(b−1 )−1 a−1 = h−1 (b−1 )−1 a−1 ∈ Ha−1 H =
b−1 H ⇐ f (Ha) = f (Hb)
Surjective:For every aH ∈ L, a right coset Ha−1 ∈ R, since aH ∈ L ⇒ a ∈ G ⇒ a−1 ∈ G ⇒
Ha−1 ∈ R. Moreover, f (Ha−1 ) = (a−1 )−1 H = aH.
f is hence a bijective correspondence.
Theorem 1.17. There is a 1-1 correspondence between any two left (or right) cosets of H in G.
Proof. Define f : Ha −→ Hb by f (ha) = hb. This map is well defined, since if h1 a = h2 a,
h1 aa−1 b = h2 aa−1 b ⇒ h1 b = h2 b ⇒ f (h1 a) = f (h2 a). Similarly, injectivity can be proved. For
every hb in Hb, h ∈ H and hence ha ∈ Ha such that f (ha) = hb. So, f is surjective.
10
Corollary. A finite group of prime order has only improper subgroups.
3. G = S3 , H = {ρ0 , ρ1 , ρ2 }
11
4. G = S3 , H = {ρ0 , µ1 } is not a normal subgroup.
Proposition 1.4. The intersection of normal subgroups is also a normal subgroup.
Proof. Let H, K E G. Let h ∈ H ∩ K and g ∈ G. Then, h ∈ H and h ∈ K. Since H, K are normal,
ghg −1 ∈ H and ghg −1 ∈ K ⇒ ghg −1 ∈ H ∩ K. This gives H ∩ K E G.
Proposition 1.6. Let M, N E G such that M ∩ N = {e}. Then, every element of M commutes
with every element of N .
Proof. It suffices to prove that for m ∈ M, n ∈ N, mnm−1 n−1 = e.
Since M E G, nmn−1 ∈ M . Also, by closure, mnmn−1 ∈ M . Similarly by closure and the inverse
axiom, N E G ⇒ mnm−1 ∈ N ⇒ mnm−1 n−1 ∈ N . This means that mnm−1 n−1 ∈ M ∩ N =
{e} ⇒ mnm−1 n−1 = e.
1. (Z, +) ∼
= (nZ, +) via φ(x) = nx
2. (R, +) ∼
= (R+ , ×) via φ(x) = ex .
3. Every infinite cyclic group is isomorphic to (Z, +).
Proof. Consider the equation x ∗ x = a ∀a. This has a solution in (R, +), viz. x = a/2. But
in (R∗ , ×), a solution does not exist if a = −1. x × x = −1 ⇒ x = i ∈
/ R∗ . If two groups are
isomorphic, the equation must have a solution in both groups.
Proof. In (R, +), O(1) = 1, O(n) = ∞ ∀n 6= 1. In (R∗ , ×), O(1) = O(−1) = 2, O(n) = ∞
otherwise. But isomorphisms conserve the order of elements. So the two groups cannot be
isomorphic.
12
6. (Q, +) (Q∗ , ×). As before, the equation x ∗ x = a can be taken. It does not have a solution
in the second group for a = 2, 3, 5, . . ..
Definition 1.15. Let φ : G1 −→ G2 be a homorphism with e1 , e2 the identity elements of G1 , G2
respectively. Then, the kernel, ker φ is the set of elements of G1 mapped by φ to e2 . i.e K =
ker φ = {x ∈ G1 |φ(x) = e2 }. The image, Im(φ) = {φ(x)|x ∈ G1 }.
Image. Suppose a, b ∈ Im(φ). Then, a = φ(g), b = φ(h) for some g, h ∈ G. Consider ab−1 =
φ(g)(φ(h))−1 = φ(g)φ(h−1 ) = φ(gh−1 ) ⇒ ab−1 ∈ Imφ. Thus, Imφ ≤ H.
Theorem 1.24. A homomorphism is injective iff its kernel is trivial i.e f is injective if f ker = {e}.
Proof. Necessary direction. Suppose f : G −→ H is injective. Assume, for a contradiction that
ker f is non-trivial, i.e it has at least one non-trivial element, g 6= e. Then, f (g) = e. But since f
is injective, f (g) = f (e) ⇒ g = e, which gives a contradiction.
Sufficient direction. Suppose ker f = {e}. Suppose f (g) = f (h) ⇒ f (g)(f (h))−1 = e ⇒
f (gh−1 ) = e ⇒ gh−1 ∈ ker f . This gives gh−1 = e ⇒ g = h, which implies that f is injective.
Example 1.18. Prove that Z/nZ ∼
= Zn .
Proof. Z/nZ = {0 + nZ, 1 + nZ, . . . , (n − 1) + nZ}. (To see why, see example 1.15). Z/nZ =
{k + nZ|k ∈ Zn }. Define f : Z/nZ −→ Zn by f (k + nZ) = k. This map is well-defined and bijective.
To see that it is a homomorphism, consider
f (k + nZ.l + nZ) = f ((k +n l)nZ) = k +n l.
f (k + nZ)f (l + nZ) = k +n l.
Theorem 1.25 (First Isomorphism Theorem). If f : G −→ H is a homomorphism, then Imf ∼
=
G/ ker f .
13